Peran Marketing Public Relations dalam Mempromosikan Produk di Marketplace Shopee pada Akun Mje Online Shop - Maryati, Maryati; Hardian, Arvin; Ekowati, Sari (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research is motivated by the rapid development of the times, where sellers must adapt to the digital advancements of the internet in the online-based sales process. One of the platforms used to sell products online is the shopee marketplace. The purpose of this research is to understand the role of marketing public relations in establishing effective communication to promote products on the shopee marketplace through the MJE Online Shop account. This study employs a qualitative approach with the content analysis method, and data collection techniques include observation, documentation, and interviews with three informants. The research findings, verified using the 4P and AIDA theories, indicate that the role of marketing public relations in price-strikethrough discount promotions shows a strong positive correlation between marketing public relations and promotion. Promotions attract consumers due to more economical prices and the convenience of purchasing their needs at affordable costs. These findings suggest that the role of marketing public relations can serve as a strategic tool for sellers on the Shopee marketplace to enhance their competitiveness and increase product sales.